KEEFEKTIFAN MODEL GAME-BASED LEARNING BERBANTUAN APLIKASI QUIZIZZ TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII DI MTS AL MADANI - Andini Hartiyana; Burhan Sidik; Laksmita Nur Afiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low ability of seventh-grade students at MTs Al Madani in writing descriptive texts, caused by limited vocabulary mastery, difficulties in developing ideas, and the use of less innovative learning methods. This study aims to examine the effectiveness of the Game-Based Learning model assisted by the Quizizz application in improving the descriptive text writing skills of seventh-grade students at MTS Al Madani. This study employed a quantitative approach with a pre-experimental one group pretest-posttest design. The sample consisted of 23 students selected using the purposive sampling technique. Data were collected through tests, namely pretest and posttest. The data were analyzed using the Wilcoxon test and N-Gain calculation. The results showed that the average pretest score of 58.04 increased to 76.09 in the posttest. The Wilcoxon test result showed a significance value of < 0.001 (p < 0.05), indicating a significant difference between the pretest and posttest results. In addition, the N-Gain score of 0.4193 was categorized as moderate improvement. Therefore, it can be concluded that the Game-Based Learning model assisted by Quizizz is effective in improving students’ descriptive text writing skills.